Safety and health practice by construction workers - Mohamad Haris, Abdullah (2017)
Construction industry has been recognized as one of the dangerous and risky industries not only in Malaysia but also around the world. Construction workers are exposed to various hazard and threat at the workplace. Hence, it is important to have a good safety and health practice at the construction site to reduce the possibility of accidents from happening. This paper aims to evaluate the factor affecting on safety and health performance at construction site, to identify the level of awareness of construction worker on safety and health at construction site and to identify the workers’ level of satisfaction towards safety and health aspect at construction site. The above study was carried out at construction site of Grade 7 contractor in Pahang. A total of 40 construction workers were used as sample. Data is obtained by using structured questionnaire. The finding reveals that the contractors have good safety and health practice. The level of awareness of workers towards safety and health are very high. Besides that, the workers are satisfied with the safety and health aspect at construction site.